2020
DOI: 10.1186/s12877-020-01850-y
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectoral inter-rater reliability of the clinical frailty scale – a Danish translation and validation study

Abstract: Background Focus on frailty status has become increasingly important when determining care plans within and across health care sectors. A standardized frailty measure applicable for both primary and secondary health care sectors is needed to provide a common reference point. The aim of this study was to translate the Clinical Frailty Scale (CFS) into Danish (CFS-DK) and test inter-rater reliability for key health care professionals in the primary and secondary sectors using the CFS-DK. Methods The Clinical F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 28 publications
(40 reference statements)
1
42
0
1
Order By: Relevance
“…However, it is likely that this bias was limited as there are several studies indicating sufficient interrater reliability of the CFS. [29][30][31][32] Although there is still some variability in interrater agreement, the CFS is prognostically relevant. 30 The present study showed an important direction for future research.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is likely that this bias was limited as there are several studies indicating sufficient interrater reliability of the CFS. [29][30][31][32] Although there is still some variability in interrater agreement, the CFS is prognostically relevant. 30 The present study showed an important direction for future research.…”
Section: Discussionmentioning
confidence: 99%
“…In our inter-rater reliability study on CFS-DK 1.2 we found little variance among raters when rating CFS levels 4 and 5, the threshold at which the term “frail” is included in headings [ 1 ]. However, a recent study on older (≥ 80 years of age) patients in intensive care units found high variance among raters when differentiating these two levels using the CFS version 1.2 [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…We consider the differences between CFS 1.2 and 2.0 versions to be minor and that the results of our recent inter-rater reliability study on CFS-DK 1.2 are likely still applicable to the 2.0 version [ 1 ]. The inter-rater reliability study used clinical vignettes to describe individuals in their habitual state, and raters were introduced to the CFS 1.2 (including an explanation of the abbreviation IADL and the importance of scoring the subject according to habitual health state) before they rated the vignettes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such changes may be subtle signs of health deterioration, and not just ageing processes. Additionally, the ‘PATINA decision tool’ includes validated health assessment scales and information on risk factors of acute disease, such as functional level (Barthel-20) [ 33 ], frailty (Clinical Frailty Scale) [ 34 , 35 ], Brief Geriatric Assessment [ 36 ], medications, falls tendency, weight, mental state, dehydration, and more. Further, the tool supports and covers areas of health care, which nurses in Denmark are obligated to assess regularly, e.g.…”
Section: Methodsmentioning
confidence: 99%